Quality improvement through implementation of poka yoke and six sigma methodology in thermal interface material coating industry - Kang, Boon Siang (2010)
This research is to study the effectiveness of implementing the Lean Manufacturing techniques to reduce process yield loss and scrap cost in Thermal Interface Material (TIM) Coating Industry. Before this research was done, the TIM coating industry always faced the problem of poor process yield and also high scrap cost. This has contributed to losses in the operation. This process yield loss and high scrap cost were due to the fact that the products produced did not meet the coating thickness specification that was set by the customers. The coating thickness is one of the most important critical to quality (CTQ) parameter. Due to this problem, this research has used Lean technique particularly Poka Yoke devices to solve this problem. The methods used are by applying Visual Management Technique and ANDON light together with laser sensors to detect and trigger the operator when the coating thickness is out of specification. The process yield and scrap cost data was taken before the implementation of Poka Yoke devices and after the implementation of Poka Yoke devices . There are then compared to see the improvements from the implementation of Poka Yoke devices. The implementation of these techniques had managed to help improve on the process yield and also in reducing the scrap cost associated with coating thickness.